Effervescent Granule Formulation Combination of Coleus amboinicus Leaves Extract and Tamarindus indica Pulp Extract - Erni Rustiani; Ulfa Nur Awinda (Tropical Biopharmaca Research Center, IPB University, 2022)
Coleus amboinicus and Tamarindus indica effectively decrease glucose in the blood with work mechanisms by reducing oxidative stress in the body. Flavonoid contains in these plants was thought to play a role as anti-diabetes. This study made an effervescent granule preparation from a mixture of Coleus amboinicus leaf extract and Tamarind (Tamarindus indica) pulp, with additional ingredients of citric acid, tartaric acid, and sodium bicarbonate. The effervescence reaction masked the extract's unpleasant taste. The three effervescent granule formulas manufacture using a dry granulation method. Each formula used a different amount of acid and base. Effervescent granule testing includes organoleptic, flow rate, angle of repose, froth height, froth time, and hedonic test. The granule quality test results show that the best effervescent granule is formula 1, which contains 7% citric acid, 14% tartaric acid, and 25% sodium bicarbonate. Formula 1 had the best high froth 0.5 cm and 2 minute 18 seconds froth time and preferred by the panelists based on aroma and taste.